If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m + -2 = n Reorder the terms: -2 + m = n Solving -2 + m = n Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + m = 2 + n Combine like terms: -2 + 2 = 0 0 + m = 2 + n m = 2 + n Simplifying m = 2 + n
| x-10/5-8=5 | | 4x/2+7=21 | | 2m-4=4n | | 0.4a=9.2 | | 80a+a^2=18a | | ((12a^-3b^4c^2)/(-4a^-7b^-2c))^-2 | | 27=(x^2-.4x) | | 3(6x-7)(3x+7)=0 | | 324=h(h+12)(h+3) | | 10x+30=20+11x | | 3(1x)=2(-2) | | 15y=3y+48 | | 9x^2+24xy+16y^2+90x-130y=0 | | B-9/12=-3 | | 1140=8x+11x | | 5(x-6)+3=33 | | 2x^2-4x=-18 | | 2p/3-5=7 | | -5y-3=4y+13 | | 6/5(8x+2)=-36 | | 8x-.5=3 | | 0=x^2-9x+25 | | 4(x+10)=60 | | 1.5=7.5 | | 6z+9-2z=10+3z-3 | | 4d-2=38 | | x(3-x)=70 | | Y=3/8*-9 | | 7d+6=62 | | -30x^6+40x^5-9x^4-48x^3+54x^2=0 | | 3x+27=17+2x | | e^2=1.4 |